Overview on antioxidant and oxidative stress markers after garlic oil supplement in suckling buffalo calves - Hamada Mahmoud YOUSIF; Ahmed Mohamed EL MAHDY; Marwa Fouad HASSAN; Mogda Kamel MANSOUR (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2023)
Calves during the suckling period have serious attention and induce immense bearing on early maturity and production. This work aimed to scrutinize the affections of garlic oil supplements on antioxidants, oxidative stress, and immune response in suckling buffalo calves. To achieve this aim we used twenty suckling buffalo calves, and divided them into two groups. The first group (n=10) did not receive any supplement, and the second group (n=10) received garlic oil as a supplement 5 mL/calf/day orally for 7 days. Whole blood and serum samples were collected on the 1st, 3rd, 5th, and 7th day of supplement from all calves. Our data showed that the supplemented garlic oil significantly increase lysated blood and serum SOD, CAT, GSH, and TAC levels, while a gradual decrease in MDA and non-significant changes in NO as indicators of oxidative stress, associated with a significant increase in serum vitamins A and E, selenium, iron, and zinc. Total protein, albumin, globulin, γ1, γ2, α1, α2 were gradually and significantly increased in comparison with the non-supplemented control group. In conclusion, garlic oil supplement have promotives effects on enzymatic and non-enzymatic antioxidant system, immunity, nutrient utilization required for immunity modulation and regulation in calves.